Performance of Male Bali Catte at Different Age By Feed Concentrate Containing Cocoa Pulp - Isdam Supriadi; Lellah Rahim; Ambo Ako; Renny Fatmyah Utamy; Muhammad Ihsan Andi Dagong (Hasanuddin Journal of Animal Science (HAJAS), 2020)
The cocoa pulp is a slimy layer that surrounds the pieces of seeds, consisting of part of water and a layer of nutritional components which is quite high, including sucrose, glucose, and a little starch. The cocoa pulp, the by-product of cocoa production, has been used to avoid environmental pollution as an organic fertilizer. However, for livestock feed, the information is so limited. Therefore, the objective of this study was to determine the performance of male Bali cattle at different ages by feed concentrate containing cocoa pulp. The experiment was carried out in a completely randomized design consisting of 3 treatments and 3 replications so that it needed 9 male Bali cattle. The treatment consisted of A1 = male Bali cattle 2 years; A2 = male Bali cattle age 3 years; and A3 = Bali cattle male age 4 years, respectively. The parameter was feed consumption, performance, daily body weight gain (DWG), and feed consumption rate (FCR). The results showed that the average feed consumption, DWG, and FCR, showed significantly different (P<0.05) on feed concentrate containing cocoa pulp. The results indicated that 4 years of male Bali cattle was good growth performance compared to 2 years and 3 years by feed concentrate containing cocoa pulp.